2021
DOI: 10.32481/djph.2021.022
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy in Delaware’s Underserved Communities

Abstract: Background and Objective: Vaccine hesitancy may be one of the greatest challenges to conquering the COVID-19 pandemic. Underserved communities across the U.S. have been suffering from the pandemic in unique ways, and vaccine hesitancy may exacerbate or prolong these issues. However, the prevalence of vaccine uptake and hesitancy in these vulnerable populations is unknown. The present study aimed to investigate: (1) prevalence of COVID vaccine uptake and COVID vaccine hesitancy in Delaware's underserved communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Eleven articles focused exclusively on Covid-19 vaccination among Black/African Americans [26,56,59,69,74,75,77,81,85,89,90], and 19 additional articles provided disaggregated data—a total of 30 sources [46-48,49,51-53,55,60,65-68,70,73,82,84,86,92]. At the structural level, 27 sources addressed the negative impacts of medical mistrust and distrust of government on Covid-19 vaccination among Black and African Americans [26,46-49,51-53,55,59,65-70,73-75,77,81,82,84-86,89,92].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles focused exclusively on Covid-19 vaccination among Black/African Americans [26,56,59,69,74,75,77,81,85,89,90], and 19 additional articles provided disaggregated data—a total of 30 sources [46-48,49,51-53,55,60,65-68,70,73,82,84,86,92]. At the structural level, 27 sources addressed the negative impacts of medical mistrust and distrust of government on Covid-19 vaccination among Black and African Americans [26,46-49,51-53,55,59,65-70,73-75,77,81,82,84-86,89,92].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the proportion of vaccine hesitant respondents in our survey might be higher than that observed in other areas. As noted earlier, many of the participants in our study live in underserved neighborhoods with low average income and educational level, and these socioeconomic characteristics might contribute to vaccine hesitancy [ 18 ]. In addition, 40% of our participants met the FCV-19S cutoff score, suggesting substantial fear of COVID-19 and higher likelihood of stress/anxiety symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…People who are willing to get vaccinated for COVID might also display greater confidence in public health measures and preventative strategies, thus making them also more likely to have been tested for COVID. For example, Wang and colleagues found that in Delaware’s underserved communities, those who have been tested for COVID were also more likely to receive COVID vaccines [ 18 ]. Lastly, in the current study, we found that essential workers have higher odds of having been tested for COVID than non-essential workers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies report vaccination rates in Blacks that are below the rates of White people. 10 For example, a Kaiser Health News report reveals that Black Americans were vaccinated at rates 2 to 3 times lower than White Americans in January of 2021. 11 However, this and other studies with similar findings require "deep dive" questions reflecting the social and structural determinants of health on which the health inequalities that were so prevalent in Black communities before and during the pandemic are necessary.…”
Section: Reframing Vaccine Hesitancy Among African Americansmentioning
confidence: 99%